2013
DOI: 10.1074/jbc.m112.435941
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cdc42 Protein Inhibitor and Its Use as a Molecular Probe

Abstract: Background: By integrating extracellular signals with actin cytoskeletal changes, Cdc42 plays important roles in cell physiology and has been implicated in human diseases.Results: A small molecule was found to selectively inhibit Cdc42 in biochemical and cellular assays.Conclusion: The identified compound is a highly Cdc42-selective inhibitor.Significance: The described first-in-class Cdc42 GTPase-selective inhibitor will have applications in drug discovery and fundamental research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 70 publications
(77 reference statements)
4
127
0
Order By: Relevance
“…1 and 2). To exert finer temporal control over Cdc42 function, we employed the Cdc42 inhibitor, ML141, which specifically inhibits Cdc42 nucleotide dissociation and activation (Hong et al, 2013), and reduced active Cdc42 levels in sea urchin embryos as measured with a Cdc42 pull-down assay (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2). To exert finer temporal control over Cdc42 function, we employed the Cdc42 inhibitor, ML141, which specifically inhibits Cdc42 nucleotide dissociation and activation (Hong et al, 2013), and reduced active Cdc42 levels in sea urchin embryos as measured with a Cdc42 pull-down assay (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…[49] This compound impairs nucleotide binding by several small GTPases with low nanomolar inhibitory constants (K i = 12.9-19.7 nm) in vitro.I na ni dentical setup,C ID29950007 (ML141, 2)w as identified as aC dc42-selective noncompetitive allosteric inhibitor (Figure 3a). [50] In this case,t he binding of 2 locks Cdc42 in an inactive conformation, thereby inducing nucleotide release and inhibition of Cdc42-mediated cellular functions such as filopodia formation or cell migration (Figure 3b). Furthermore, 2 proved useful for combination with colony-stimulation factor (G-CSF) in the mobilization of hematopoietic stem and progenitor cells.…”
Section: Interference With Nucleotide Bindingmentioning
confidence: 98%
“…However, the experiment involves an ucleotideremoving gel-filtration step,s oi td oes not clearly show whether the inhibitor can compete with cellular nucleotide concentrations. [71] To achieve cell penetration, SML-10-70-1(5), acaged phosphoramidate derivate of 4,was synthesized, which impairs Akt and ERK phosphorylation in aH 358 cell line at ac oncentration of 100 mm and proliferation in KRas G12C mutant H358 and H23 cells with ah alf-maximum effective concentration (EC 50 )o f2 7mm and 48 mm,r espectively.I nterestingly, 5 also shows antiproliferative effects in A549 cells,w hich contain aG 12S mutation, thus indicating additional nonselective modes of action. [59] By using at ethering approach, another set of covalent inhibitors was identified that make use of the G12C mutation as ac hemically targetable anchor.…”
Section: Mutant-selective Targeting Through Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Y-27632 specifically inhibits the RhoA/Rho-associated coiled-coil-containing protein kinase (ROCK), one of the downstream RhoA effectors (42,43). ML141 is a selective and allosteric inhibitor for Cdc42 (44), and AZA1 inhibits the activation of Cdc42 and Rac1 (45). NSC23766 inhibits the Rac1-specific GEF but has no effect on RhoA and Cdc42 activity (46,47).…”
Section: Resultsmentioning
confidence: 99%